2020
DOI: 10.1111/are.14617
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition, osmolality, Na + , K + ‐ATPase activity, cortisol content and antioxidant status of rainbow trout ( Oncorhynchus mykiss ) in response to various dietary levels of eicosapentaenoic acid and docosahexaenoic acid

Abstract: This study was conducted to evaluate the effect of dietary eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels on the fatty acid composition, salinity tolerance and antioxidant status of rainbow trout (Oncorhynchus mykiss). Four diets were formulated with total EPA and DHA contents of 5. 41, 9.55, 13.97 and 17.88 g/ kg (abbreviated as ED-5.41, ED-9.55, ED-13.97 and ED-17.88 respectively). Rainbow trout (initial weight of 90.61 ± 9.25 g) were fed the experimental diets for 8 weeks to accumulate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Serum Biochemical Parameters, Biometric Indices, and Hepatic Histological Assay. Serum biochemical analysis showed that the contents of HDL-C, LDL-C, TG, and TC were significantly increased with the increase of dietary ostf1: osmotic stress transcription factor 1; 2 ncc: Na +/ Clcotransporter; 3 aqp1: aquaporin; 4 nkaα: Na + /K + -ATPase; 5 elovl4a: elongase 4a; 6 elovl4b: elongase 4b; 7 fads2: fatty acid desaturase 2; 8 sirt1: silent regulator 1; 9 pparα: peroxisome proliferator activated receptors alpha; 10 srebp-1: sterol regulatory element-binding protein 1; 11 Cu/Zn sod: Cu/Zn superoxide dismutase; 12 Mn sod: Mn superoxide dismutase; 13 cat: catalase; 14 foxO1: forkhead box 1; 15 grp78: glucose regulated protein 78; 16 atf6: activating transcription factor 6; 17 xbp1: X-box binding protein 1; 18 ire1α: inositol requiring enzyme-1; 19 nf-κb: nuclear factor kappa b; 20 tnfα: tumor necrosis factor alpha; 21 tgf-β1: transforming growth factor β1; 22 il-10: interleukin-10; 23 il-1β: interleukin-1 beta; 24 jnk: c-Jun N-terminal kinase; 25 bcl-2: B cell leukemia2; 26 bax: bcl 2-associated X. 7 Aquaculture Nutrition lipid levels under low-salinity environment (P < 0:05) (Figure 4(a)).…”
Section: Fatty Acid Composition and Lc-pufa Biosyntheticmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum Biochemical Parameters, Biometric Indices, and Hepatic Histological Assay. Serum biochemical analysis showed that the contents of HDL-C, LDL-C, TG, and TC were significantly increased with the increase of dietary ostf1: osmotic stress transcription factor 1; 2 ncc: Na +/ Clcotransporter; 3 aqp1: aquaporin; 4 nkaα: Na + /K + -ATPase; 5 elovl4a: elongase 4a; 6 elovl4b: elongase 4b; 7 fads2: fatty acid desaturase 2; 8 sirt1: silent regulator 1; 9 pparα: peroxisome proliferator activated receptors alpha; 10 srebp-1: sterol regulatory element-binding protein 1; 11 Cu/Zn sod: Cu/Zn superoxide dismutase; 12 Mn sod: Mn superoxide dismutase; 13 cat: catalase; 14 foxO1: forkhead box 1; 15 grp78: glucose regulated protein 78; 16 atf6: activating transcription factor 6; 17 xbp1: X-box binding protein 1; 18 ire1α: inositol requiring enzyme-1; 19 nf-κb: nuclear factor kappa b; 20 tnfα: tumor necrosis factor alpha; 21 tgf-β1: transforming growth factor β1; 22 il-10: interleukin-10; 23 il-1β: interleukin-1 beta; 24 jnk: c-Jun N-terminal kinase; 25 bcl-2: B cell leukemia2; 26 bax: bcl 2-associated X. 7 Aquaculture Nutrition lipid levels under low-salinity environment (P < 0:05) (Figure 4(a)).…”
Section: Fatty Acid Composition and Lc-pufa Biosyntheticmentioning
confidence: 99%
“…Moreover, the rate of ions entering and leaving cells can be affected to enhance and improve the osmoregulatory ability, through changing the membrane surface area and regulating Na + /K + -ATPase (NKA) activity [10]. Previous studies suggested that the changes of lipid ratio in membrane led to increase of membrane surface area and related ion pumps, thus improving ion transport rate and osmotic pressure regulation ability [11][12][13]. Therefore, optimal dietary lipid level not only can promote growth performance of farmed fish but also can improve the ability of fish to adapt to salinity changes; in turn, excessive dietary lipid intake could increase the burden on the fish body and reduce its ability to adapt to environmental changes [14]; hence, there is an urgent need to understand the optimal dietary lipid requirement for aquatic animals in different environments, for instance, low-salinity environment.…”
Section: Introductionmentioning
confidence: 99%
“…The sh were subjected to temperature acclimation in freshwater for six weeks. Immediately after acclimation, the salinity of all tanks was increased to 15 ppt from 0 ppt by mixing with seawater (salinity 30 ± 1 ppt), and then further increased to 30 ppt from 15 ppt at a rate of 3 ppt per day, according to the method described by Huang et al [8]. The water at the desired salinity was prepared in advance and pumped into the tanks.…”
Section: Experimental Designmentioning
confidence: 99%
“…The discovery of the Yellow Sea Cold Water Mass opened up the possibility of offshore salmon mariculture [ 3 , 4 ], one of the pivotal stages of this project is the ‘mountain-sea relay’ mode, in which salmon are hatched and bred until the juvenile stage in freshwater in mountainous areas, transferred to seawater, and fattened to commercial size. Previous research has reported that the seawater tolerance of salmonids can be influenced by life stage [ 5 ], photoperiod [ 6 ], salinity stimulation [ 7 ], nutritional status [ 8 , 9 ], and temperature change [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation